Enhancing Corn Yield and Soil Quality in Irrigated Semiarid Region with Coal Char and Biochar Amendments - Resham B. Thapa; Samir Budhathoki; Chandan Shilpakar; Dinesh Panday; Bouzeriba Alsunuse; Sean X. Tang; Peter D. Stahl (Soil Systems, 2024)
Sustainable use of croplands is facing a challenge to maintain organic carbon (C) in soil. Pyrolyzed coal or coal char (CC) is a porous C material produced from the pyrolysis of coal containing high organic C, large surface area, and low bulk density like biochar (BC). This study evaluates corn (Zea mays L.) grain yield and selected soil properties in soil amended with CC and BC at two rates (22 and 44 Mg ha−1) with farmyard manure (FM) (66 Mg ha−1) and without FM addition. This field experiment was performed in sandy loam soil at the University of Wyoming’s Sustainable Agricultural Research and Extension Center (SAREC), Lingle, WY, USA. Two years of field study results indicated CC and BC applied at 22 Mg ha−1 with FM resulted in significantly greater average corn grain yields (13.04–13.57 Mg ha−1) compared to the no char’s treatment (11.42 Mg ha−1). Soil organic matter (SOM) content was significantly greater in the higher application rates of CC and BC than in treatments without chars. Overall, soil nitrate nitrogen (NO3-N), phosphorous (P), and potassium (K) were found significantly greater in CC and BC co-applied with FM treatments. Soil water-holding capacity (WHC) significantly improved in sandy loam soil (up to 27.6% more than the no-char treatment) at a greater concentration of char materials. This study suggests that char materials applied at a moderate rate (22 Mg ha−1) with FM can improve soil properties and crop yield.